2011
DOI: 10.1177/0146167211408922
|View full text |Cite
|
Sign up to set email alerts
|

Time Crawls When You’re Not Having Fun

Abstract: All people have to complete dull tasks, but individuals who feel entitled may be more inclined to perceive them as a waste of their "precious" time, resulting in the perception that time drags. This hypothesis was confirmed in three studies. In Study 1, participants with higher trait entitlement (controlling for related variables) thought dull tasks took longer to complete; no link was found for fun tasks. In Study 2, participants exposed to entitled messages thought taking a dull survey was a greater waste of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…fact, some researchers see entitlement as a specific form of self-focus (e.g., O'Brien, Anastasio, & Bushman, 2011). Further evidence shows that victims tend to be less prosocial.…”
Section: Empirical Evidence For a Stronger Self-focus Of Victimsmentioning
confidence: 99%
“…fact, some researchers see entitlement as a specific form of self-focus (e.g., O'Brien, Anastasio, & Bushman, 2011). Further evidence shows that victims tend to be less prosocial.…”
Section: Empirical Evidence For a Stronger Self-focus Of Victimsmentioning
confidence: 99%
“…The experiences of feeling detached from one’s body and of “sinking into pictures” were assessed by single items constructed for the purpose of this study. These items were rated on a 4-point Likert scale ranging from “not at all” to “completely.” For the assessment of subjectively experienced waste of time the item “In your honest opinion, do you think this survey was a waste of time?” was used ( O’Brien et al, 2011 ). In addition, participants in the time-awareness conditions were asked if they used counting to estimate time correctly.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, other research has demonstrated that time seems to drag when individuals are not enjoying themselves (Danckert & Allman, 2005;O'Brien, Anastasio, & Bushman, 2011;Ratcliffe, 2012). Danckert and Allman (2005) found that participants who were bored experienced time as passing more slowly than those who were not bored.…”
Section: Time Flies When We Are Having Funmentioning
confidence: 97%